The development of teaching Arabic through Higher Thinking (HoTS) for students of the Islamic Boarding School in South Sumatra - Wasilah, Wasilah (Magister Pendidikan Agama Islam Universitas Islam Nusantara, 2022)
This research is motivated by the need to overcome the gap between ideal conditions and real conditions in the field, especially problems in learning Arabic. In this case, learning the nahwu rules with the source of learning is the book of Imrity. This book contains 254 nahwu rules with explicit explanations. The learning objectives are still in the level one cognitive domain, namely memorizing. So this research develops a learning model that aims to improve their cognitive at C4, C5 and C6 levels. This research method uses the development and research model developed by Borg and Gall. In its development research focuses on developing teaching materials. The results of this study suggest that the results of the validation of the teaching materials developed received a score of 90, which is very good. The results of the media validation included the display aspect of good value with 70 while the value of the usage aspect had good value with a score of 67. Based on the test results in the control class a score of 76 and in the Experiment class a score of 86. So the results of the analysis with SPSS 22 obtained a value of Sig.(2- tailed) of 0.000 <0.05 so that the test results on decision making in the T-Test test are Ha accepted and Ho rejected. Rejecting Ho and accepting Ha, the development of HOTS-based Arabic learning can help students learn Arabic at C4, C5 and C6 levels.